The formation of interregional trade agreements: which factors provoke trade blocs to cooperate? - Abilkassymov, Bekzada (Nazarbayev University School of Sciences and Humanities, 2016)
Recently we have observed cooperation between trade blocs as the European Union, the Andean Community, Mercosur, ASEAN and others. These actors have started to negotiate a possibility of trade agreements between each other. What did provoke regional trade blocs to form and proliferate this kind of arrangements in trade? How it can be explained through a theoretical standpoint of international relations? I attempt to answer for these questions in this paper. Generally, the research constructs an explanation for the formation of interregional trade agreements through bargaining theory by emphasizing the roles of trade gains, depth of integration within a bloc, a level of developments, membership and disputes history in the WTO. The results demonstrate positive and significant influence of trade gains, depth of integration and membership in the WTO, while disputes history affected significantly but negatively interregional cooperation. There is an important implication for policy-makers in applying this information for calculation of possible trade agreements between blocs
Keywords: regional trade blocs; interregional trade agreement; interregional cooperation; inter-blocs cooperation; trade gains; depth of integration; a level of development; the World Trade Organization; disputes history